Hydrogen and Fuel Cell Technologies and Market Perspectives - Töpler, Johannes; Lehmann, Jochen (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book introduces readers to hydrogen as an essential energy carrier for use with renewable sources of primary energy. It provides an overview of the state of the art, while also highlighting the developmental and market potential of hydrogen in the context of energy technologies; mobile, stationary and portable applications; uninterruptible power supplies; and in the chemical industry. Written by experienced practitioners, the book addresses the needs of engineers, chemists and business managers, as well as graduate students and researchers.